Etika Bisnis Islam Al-Shāh Waliyullāh al-Dahlawī - Atep Hendang Waluya (Universitas Islam Darul 'ulum Lamongan, 2024)
Islamic teachings consist of aqidah, ibadah, muamalah and morals. Ethics or morals in Islam are part of maqāsid al-sharī‘ah. Al-Dahlawī was one of the mujaddids of Islam at the end of the time of the Mongol Emperor Al-Muẓaffir who contributed ideas related to Islamic socio-economics which was termed irtifaqāt. In Hujjat Allāh al-Bālighah, apart from talking about irtifaqāt, al-Dahlawī also talks about the ethics of achieving life which is the main basis before the second irtifaqāt. According to al-Dahlawī, ethics in business is needed so that there is healthy competition and no party is disadvantaged in obtaining wealth. The Islamic business ethics are to keep business away from gambling, usury, tadlīs, gharar, to keep business away from buying and selling which is haram, reducing and leading to immorality, not reducing measures and scales, not committing talaqqī al-rukbān, ihtikār, and perjury.